Budaya On dan Giri pada Tokoh Sen dan Chihiro dalam Anime Spirited Away Karya Hayou Miyazaki - Dhea Lania; Umi Handayani (Prodi Sastra Jepang Universitas Ngudi Waluyo, 2024)
Anime is well known as a typical Japanese animation created with moving images that resemble human beings. Anime has a certain appeal as entertainment that entertains audiences. From another angle, however, anime also provides the moral and cultural messages that its creators wish to convey through each character's story and characterization.